Rocks of ages : developing rock art tourism in Israel - Schmidt, Joshua (Ethnologist), (Archaeopress Archaeology, 2022)
This volume presents the findings of an interdisciplinary project aimed at safeguarding the future of this unique resource. Cultural heritage in the Negev desert region of Israel is potentially under threat from a number of social, political and economic activities such as militarization, settlement and tourism, resulting in significant environmental change. The cultural heritage and archaeology extend back at least a quarter of a million years but also include a unique engraved rock art assemblage that dates to at least 3000 BCE. These engravings form a clear association with other relic monuments including prehistoric and protohistoric settlements, agricultural and irrigation regimes, and the remnants of a nomadic way of life.